Essential aspects of union freedon in Venezuelan labor relations - Pernía Hoyo, Nuvia; Alvarado Pinto, Diony (Gaceta Laboral, 2023)
The present documentary research work aims to hermeneutically describe and analyze the essential elements of collective freedom of association, from the ollective subjects as their holders, within the normative and practical problems derived from the involvement of labor actors. At first, the essential rights that such freedom includes in the substantive labor law and the current regulations are dealt with in a timely manner; to later develop the performance of international organizations regarding the regulations and practice of such rights in Venezuela, in the specific case of the thirteenth Commission of Inquiry appointed by the Board of Directors of the International Labor Organization. And finally, expose actions of civil society around the Decree with Rank, Value and Force of Organic Law of Labor, Workers and Workers, and the more general features of a legislative initiative of the labor movement, of a preliminary draft of the Organic Law of Freedom of Association, as a response to the existing problem. Coming to the conclusion that the labor movement must rebuild itself and resume its historical role in labor relations, to press the necessary changes in the adverse Venezuelan normative and practical context, to seek to achieveeffective union freedom.